Classification of Personality based on Beauty Product Reviews Using the TF-IDF and Naïve Bayes (Case Study : Female Daily) - Novia Russelia Wassi; Adiwijaya Adiwijaya; Mahendra Dwifebri Purbolaksono (Journal of Data Science and Its Applications, 2020)
A person's personality is an important parameter to determine the character of each person and also as an assessment in various ways. In this day and age personality can not only be known from psychological tests, but also can be known in various ways. One way is through reviews presented in electronic media. In this study, a person's personality was classified into three "Big Five" personality groups, namely: Openness, Conscientiousness, and Extraversion using the Naïve Bayes method and TF-IDF as Feature Extraction. The results of the classification that have been done get 81% accuracy with preproccessing scenarios using Stemming and Stopword, TF-IDF unigram, and BernoulliNB classifier type.